GAMBARAN VIABILITAS DAN VISKOSITAS SPERMATOZOA PADA CAIRAN SEMEN PEMINUM ALKOHOL DI KOTA BENGKULU TAHUN 2023 - Febriyanto, Tedy; Laksono, Heru; Hidayatullah (Public Health Department, Faculty of Health Science University Muhammadiyah Bengkulu, 2023)
Background: The problem of fertility, especially in men or infertility is a very serious public health problem at this time. One of the causes is consuming alcohol. According to the Central Statistics Agency (BPS), per capita alcohol consumption for Indonesians aged 15 years and over in 2021 is 0.36 liters and in Bengkulu province itself it is 6.52%. This made the writer interested in knowing the description of viability and viscosity in the semen of alcoholic drinkers in Bengkulu City. Method: The sampling technique in this study used a purposive sampling method, and the sample used was liquid semen of alcoholic drinkers as many as 36 samples. Result and Discussion: The results of observations from 36 samples showed that the majority of the percentage of samples who drank alcohol were 75% heavy drinkers with abnormal spermatozoa viability (75%) and with abnormal spermatozoa viscosity (72%). Conclusion: The results of a study of 36 samples of semen fluid drinkers in Bengkulu City, it was found that most of the respondents drank alcohol (75%) including heavy drinkers with abnormal spermatozoa viability (75%) and with abnormal spermatozoa viscosity (72%). Keywords : Alcohol drinker ,Sperm, Viability, Viscosity